Impact of the COVID-19 Pandemic on the Efficiency of the Banking Sector: A Study in the Context of Bangladesh - Hossain, Mohammad Sabbir (Finance & Economics Review, 2025)
Purpose: The banking sector plays a significant role in strengthening a nation’s economic growth. However, it faced special challenges during the COVID-19 pandemic, which affected banks’ efficiency. Thus, this study aims to measure the effects of COVID-19 on banks’ efficiency during and after the pandemic in Bangladesh. Methods: The banking sector’s technical efficiency was evaluated using the meta frontier Data Envelopment Analysis approach, based on secondary data from 23 commercial banks listed on the Dhaka Stock Exchange (DSE). Banks were selected based on the percentage of market share in the Banking industry. The data covering 2020-2024 were obtained from publicly available annual reports and financial statements. Results: Findings indicate that banks in Bangladesh were significantly more efficient after COVID-19 and that their performance has recovered. They have an average technical efficiency score of 0.63, compared to 0.51 during the pandemic. Implications: These findings have the potential to help policymakers find opportunities for profit increase and help develop early preventive measures during crises. Originality: This pioneering study in Bangladesh assessed banking efficiency after COVID-19.